EMPATI SISWA MENGGUNAKAN MODEL PEMBELAJARAN IOC DAN ROLE PLAYING DENGAN MEMPERHATIKAN IQ - Amalya Oudri Windi; Edi Purnomo; Yon Rizal (FKIP Unila, 2015)
The goal this research is to know effectiveness of the IOC learning model and role playing to improve student empathy with regard intelligence quotient eighth grade students of SMP Negeri 20 Bandarlampung years 2014/2015. Methods used in this study was a quasi-experimental. Population of this study amounted six classes, samples taken by cluster random sampling amounted two classes. The results showed: (1) theres a difference empathy students given the IOC with a given of role playing, (2) empathy students are given IOC higher than students given role playing for students who have a high level of intelligence quotient in integrated social learning, (3) empathy students are given role playing is higher than a given student IOC for students who have a low level of intelligence quotient in integrated social learning, and (4) there is an interaction between learning model with an intelligence quotient of the empathy students.Penelitian ini bertujuan untuk mengetahui efektivitas model pembelajaran IOC dan role playing untuk meningkatkan empati siswa dengan memperhatikan intelligence quotient siswa kelas VIII SMP Negeri 20 Bandarlampung Tahun Ajaran 2014/2015. Metode penelitian ini adalah eksperimen semu. Populasi penelitian ini berjumlah 6 kelas, sampel diambil berdasarkan cluster random sampling berjumlah 2 kelas. Hasil penelitian menunjukkan: (1) ada perbedaan empati siswa yang diberikan IOC dengan siswa yang diberikan role playing, (2) empati siswa yang diberikan IOC lebih tinggi dibandingkan dengan siswa yang diberikan role playing bagi siswa yang memiliki tingkat intelligence quotient tinggi dalam pembelajaran IPS Terpadu, (3) empati siswa yang diberikan role playing lebih tinggi dibandingkan dengan siswa yang diberikan IOC bagi siswa yang memiliki tingkat intelligence quotient rendah dalam pembelajaran IPS Terpadu, dan (4) ada interaksi antara model pembelajaran dengan intelligence quotient terhadap empati siswa.Kata kunci: empati, IOC, IQ, role playing